The presence of new threat for public transportation services in the industrial age 4.0 - Wildan Dwi Dermawan; Faizal Haris Eko Prabowo (KINERJA, 2019)
Business, technology and transportation systems growth rapidly along with the times. At present, transportation is a means that cannot be separated from the daily activities of human life. There are two types of transportation, namely conventional transportation and online transportation. The purpose of this study is to analyze and find out the differences in income earned, maximum income, minimum income and average income obtained by public transport drivers before and after online transportation. This study uses a comparative method to describe before and after revenue of public transportation drivers. The results show that there was a decreasing in the average driver's income of public transport by 60.5%, a decrease in maximum income obtained by public transport drivers by 60% and a decrease in minimum income obtained by public transport drivers by 50%. Decreasing the revenue of drivers of public transport after the emergence of new technology and the operation of online transportation caused a change in the interest of passengers in using public transportation. There are several reasons for the shifting of angkot passengers using online transportation services including travel time, lack of awareness and discipline of public transportation drivers, unscheduled fuel filling, forced transfer of passengers, and public transportation facilities.